Pengaruh Penggunaan Limbah Kecambah Kacang Hijau Sebagai Pakan Subtitusi Terhadap Produktivitas Itik Peking (Anasplatyrhynchos) - Tri Rumiyani; Yana Sukaryana; Cintia Agustin Patria (Musamus Journal of Livestock Science, 2022)
The aim of research is to know effect green bean sprouts waste (GBSW) to body weight, consumption, feed conversion, R/C and B/C Peking Duck (anasplatyrhychos). Material of research used 80 DOD peking duck. Experimental design for this research used with completely randomized design (CRD) one way with three treatment T1(0% GBSW),T2(5%GBSW),T3(10% GBSW), and T4(15% GBSW) with 4 replicated each of them U1, U2 U3 and U4 and used Duncan. Peking duck age 0-2 weeks maintenance with intensive system and give them commercial feed. Alternative feed gived them in 2-8 weeks age, and giving for feed three times a day. The result of research showed that effect green bean sprouts not significant Different (P>0.05) to body weight, feed consumption and feed conversion Peking duck. The conclusion for this research is green bean waste for alternative feed in Peking duck not influence for body weight, feed consumption, feed conversion.